A32 EMPAGLIFOZIN IMPROVES GASTROINTESTINAL INFLAMMATION IN A MOUSE MODEL OF COLITIS. (4th March 2021) - Madsen, K; Dang, H; Hotte, N; Mocanu, V; Ferdaoussi, M; Thiesen, A; Dyck, J
Abstract: Background: Empagliflozin (EMPA) is a highly selective sodium glucose cotransporter-2 (SGLT2) inhibitor and is increasingly being utilized as an antihyperglycemic agent in the management of type 2 diabetes. Interestingly, it has been demonstrated in human trials that EMPA treatment exerts potent cardioprotective effects by reducing cardiac inflammation independently of glycemic control. Further, EMPA has also been shown to suppress LPS-induced renal and systemic inflammation in an animal model. Based on these findings, we hypothesized that EMPA treatment may also be effective in reducing gut inflammation. Aims: The aim of this study was to examine the effects of treatment with EMPA on gastrointestinal inflammation in an animal model of inflammatory bowel disease and to determine mechanistic insights regarding its direct effects on gut cytokine secretion. Methods: Adult male and female IL-10 -/- mice with established colitis were treated with a daily gavage of EMPA (10mg/kg; n=10) or vehicle (n=10) for 14 days. Disease activity was assessed by measurement of mouse weight, colonic weight and length, histological score, cytokine levels in colonic homogenate and lipocalin-2 levels in stool. To examine for possible direct effects of EMPA, colonic explants from wild-type (n=8) and IL-10 -/- (n=8) mice were incubated with increasing doses of EMPA (0.1–5 µM) ± LPS (10µg/ml) for 2 hours and tissue levels of IL-1β and TNFα protein measured by ELISA. Results: After 14 days EMPA treated IL-10 -/- mice had a significant improvement in colonic inflammation as evidenced by decreased colonic weight to length ratio (p=0.019), decreased fecal lipocalin-2 (p=0.03), as well as decreased enterocyte injury (p=0.01), decreased lamina propria neutrophils (p=0.01) and decreased total histological score (p=0.006). EMPA treated mice also maintained their weight over the 14 days while untreated mice continued to lose weight (p=0.04). There were no significant differences in colonic homogenate levels of TNFα, IL-1β, or IL-6 or in blood glucose levels between EMPA-treated mice and controls. In addition, EMPA did not suppress levels of basal or LPS-induced TNFα and IL-1β in colonic explants from either wild-type or IL-10 -/- mice suggesting that the beneficial effects in IL-10 -/- mice were not due to direct effects of EMPA on colonic TNFα or IL-1β cytokine levels. Conclusions: EMPA treatment dramatically improved histologic and fecal inflammatory markers and maintained body weight in adult IL-10 -/- mice with established colitis. These findings suggest further investigations into the effects of EMPA in treating gut inflammation are warranted. Funding Agencies: CAG, CIHR